2017
DOI: 10.18172/cig.3202
|View full text |Cite
|
Sign up to set email alerts
|

Pleistocene Glaciations in the Northern Tropical Andes, South America (Venezuela, Colombia and Ecuador)

Abstract: ABSTRACT. This article presents an overview of glaciation studies in the northern tropical Andes (Venezuela, Colombia and Ecuador)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 49 publications
(132 reference statements)
0
9
0
Order By: Relevance
“…The first two contributions describe the deglaciation of the glaciers situated in the five countries of the Northern and Central Andes. Angel et al (2017) present the state of knowledge in the Northern Andes, i.e. in Venezuela, Colombia and Ecuador.…”
Section: The Deglaciation Of the Andean Mountains And Tierra De Fuegomentioning
confidence: 98%
See 3 more Smart Citations
“…The first two contributions describe the deglaciation of the glaciers situated in the five countries of the Northern and Central Andes. Angel et al (2017) present the state of knowledge in the Northern Andes, i.e. in Venezuela, Colombia and Ecuador.…”
Section: The Deglaciation Of the Andean Mountains And Tierra De Fuegomentioning
confidence: 98%
“…The evidence of glacial advances that coincide with the Younger Dryas is very limited in South America. There is evidence of a cold climate in the Northern Andes at that time and some glacial advances have been observed, but not in a generalized way (Angel et al, 2017). Mark et al (2017) found that glaciers in Peru and Bolivia retreated significantly during the YD due to arid climates.…”
Section: Effects Of the Younger Dryasmentioning
confidence: 99%
See 2 more Smart Citations
“…This increase in relief is consistent with regional paleogeographic reconstructions [56], which show the Panama Arc colliding with North Andes (Figure 25), raising the relief of the Western and Central Cordilleras, increasing the volumes of sediments eroded and transported by the Cauca and Magdalena rivers to the MSF area. In addition to the regional process of raising the Central and Western Cordilleras, this process could be extended to the Eastern Cordillera, providing the conditions for the accumulation of glacial deposits at 2.6 Ma [118], [119], coincident with the transition between the maximum relative sea level rise and the beginning of a major sea level fall that marks the top of the S05 sequence (Figures 8 and 15). [116].…”
Section: Sedimentary Sequences Accumulated In the Cb After The Union Of The Cauca -Magdalena Riversmentioning
confidence: 99%